Information technology at work Big W. - Media Australia (Production company); Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2000)
"This program examines how Big W uses information technology to manage its retail operations and explains the importance and role of IT within Big W; how IT has changed large retailing over the past decade; how IT technology such a bar-code scanners have revolutionised the sales process; how RF handguns and shelf-edge labels are used to compute essential data for stock inventory, ordering, receivals and warehousing; how sales data analysis helps buyers to plan orders, and predict future customers buying patterns; how IT is used for other Big W store support services - such as communications, payroll, rosters, electronic banking and EFTPOS; the future of IT in retail; security issues; and finally: the costs and benefits of a large-scale retail IT system for Big W."--Container.
Keywords: Big W (Firm); Information technology -- Australia; Stores, Retail -- Australia